Modelling of quadcopter in crosswinds - Goh, Jin An (Nanyang Technological University, 2024)
The utilization of quadcopters has been steadily increasing across various industries, prompting extensive research into their aerodynamic properties to optimize their functionality. In this study, a simplified quadcopter model will be subjected to varying levels of crosswind and studied to obtain its aerodynamic properties through the use of computational fluid dynamics. Following that, the aerodynamic forces will be used to create an aerodynamics model to predict how a quadcopter will react at various angles of attack.